Critical Issues for the Development of Sustainable E-health Solutions - Wickramasinghe, Nilmini; Bali, Rajeev; Suomi, Reima; Kirn, Stefan; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Critical Issues for the Development of Sustainable E-Health Solutions Nilmini Wickramasinghe, editor    Health care companies want to deliver their services with greater efficiency and cost-effectiveness. Consumers want services that are effective, responsive, convenient, and worth the cost. In response to these demands, web-based and other electronic technologies are revolutionizing health care services. Critical Issues for the Development of Sustainable E-Health Solutions surveys this rapid transformation as it is occurring worldwide.   Focusing on new applications in consumer-centered health care in North America, Europe, and Asia, the book demonstrates how electronic innovations can balance business objectives (e.g., low cost, improved performance management) while attending to consumer needs (e.g., access, quality, and value). Keeping technical jargon to a minimum, chapter authors dissect the impact of e-solutions on both sides of the health care system, and the keys to successful adaptation and sustainability. Facilitators and obstacles to IT changeovers based on economic, cultural, and other factors are identified in detail. And the book warns realistically against the pitfalls of designing and implementing tech-based platforms in systems not yet ready to make such changes.   A sampling of topics covered: A strategic model for health care IS design. Online discussion forums as a means of peer support. Improving web accessibility for disabled people. Knowledge management: often neglected yet crucial to e-health. Business models for electronic health care services: examples from Germany. A comprehensive approach to the IT-clinical practice interface.   With its wide scope of innovative ideas, Critical Issues for the Development of Sustainable E-Health Solutions is a path-breaking text for health care administrators and researchers in health care management, health policy, and health services.
Foreword -- Part I Innovation & Process -- Chapter 1. Improving e-performance management in healthcare using intelligent IT solutions -- Chapter 2. An intelligence e- risk detection model to improve decision efficiency in the context of the orthopaedic operating room -- Chapter 3. Healthcare Information Systems Design: Using a Strategic Improvisation Model -- Chapter 4. Assimilation Of Healthcare Information Systems (HIS): An Analysis And Critique -- Chapter 5. e-Health in China: an evaluation -- Chapter 6. Improving The Process Of Healthcare Delivery in An  Outpatient Environment: The Case of a Urology Department -- Chapter 7. Adaptations For E-Kiosk Systems In Germany To Develop Barrier-Free Terminals For Handicapped Persons -- Part II Design & Organisation -- Chapter 8. Collaborative Approach For Sustainable Citizen-Centered Health Care -- Chapter 9. Strategies and Solutions in eHealth: A Literature Review -- Chapter 10. Online Discussion Forum as a Means of Peer Support -- Chapter 11. Designing Persuasive Health Behavior Change Interventions -- Chapter 12. Accessibility In The Web For Disabled People -- Part III People -- Chapter 13. Knowledge Management: often neglected but crucial to eHealth -- Chapter 14. Patient Empowerment – A Two Way Road -- Chapter 15. Citizen ePOWERment -- Chapter 16. E-health: Focusing On People-Ceintric Dimensions -- Chapter 17. A Model of Estimating the Direct Benefits of Implementing Electronic data exchange of EMRs and State Immunization Information Systems -- Part IV IS/IT -- Chapter 18. Business Models for Electronic Healthcare Services in Germany -- Chapter 19. Smart Objects in Healthcare – Impact on Clinical Logistics -- Chapter 20. Agency Theory in E-Healthcare and Telemedicine: A Literature Study -- Chapter 21. Cost Accounting and Decision Support for Healthcare Institutions -- Chapter 22. A Comprehensive Approach to the IT – Clinical Practice Interface -- Epilogue.
Keywords: Health informatics; Health Informatics